Insights into the evolution of Greek style table olives microbiome stored under modified atmosphere: Biochemical implications on the product quality. (December 2021) - Michailidou, Sofia; Trikka, Fotini; Pasentsis, Konstantinos; Petrovits, George Economou; Kyritsi, Mary; Argiriou, Anagnostis
Abstract: Olives are among the main components of the Mediterranean diet, rich in micronutrients and powerful antioxidants; their unique organoleptic properties and high nutritional value have increased table olive consumption worldwide. The purpose of this work was to study the microbiological and biochemical changes in Greek-style 'Kalamata' table olives, throughout different time-points of the shelf life of the product, packaged under modified atmosphere. Results revealed the prevalence of lactic acid bacteria ( Lactobacillus spp.) from T0 and after the end of the product's shelf life, with L. parafarraginis being the dominant species, ranging from 37.8% to 49.8%. Concerning the eukaryotic populations, antagonistic interactions were observed among the dominant genera i.e. Pichia, Cladosporium and Saccharomyces . While Candida pseudolambica was the most abundant species up to T6, it was gradually displaced by Brettanomyces custersianus at T12 and T18. The significant decrease of total phenol content and a-tocopherol at T12, reflected the increment of Lactobacillus and yeast populations. The dominance of Lactobacillus spp. And B. custersianus at T18 was also depicted on the significant increase of hydroxytyrosol. The content of some fatty acids was shown to be affected by the yeast populations while the concentration of maslinic and oleanolic acid remained intact throughout storage. The combined approach of amplicon metabarcoding and biochemical analyses of naturally fermented olives packaged under modified atmosphere, enabled us to better understand the microbial competitions and interactions and the biochemical changes that accompany these transitions, hence, defining the quality of the end product offered to the consumer. Highlights: Kalamata table olives packaged under modified atmosphere. Microbiome's activity was associated with changes of biochemical parameters. Amplicon metabarcoding and biochemical analyses for product quality assessment. Prevalence of lactic acid bacteria throughout the product's shelf life. Antagonistic interactions among yeasts (i.e. Pichia, Cladosporium, Saccharomyces ).